A Road Map toward Field‐Effect Transistor Biosensor Technology for Early Stage Cancer Detection. Issue 10 (6th September 2022) - Eswaran, Muthusankar; Chokkiah, Bavatharani; Pandit, Santosh; Rahimi, Shadi; Dhanusuraman, Ragupathy; Aleem, Mahaboobbatcha; Mijakovic, Ivan
Abstract: Field effect transistor (FET)‐based nanoelectronic biosensor devices provide a viable route for specific and sensitive detection of cancer biomarkers, which can be used for early stage cancer detection, monitoring the progress of the disease, and evaluating the effectiveness of therapies. On the road to implementation of FET‐based devices in cancer diagnostics, several key issues need to be addressed: sensitivity, selectivity, operational conditions, anti‐interference, reusability, reproducibility, disposability, large‐scale production, and economic viability. To address these well‐known issues, significant research efforts have been made recently. An overview of these efforts is provided here, highlighting the approaches and strategies presently engaged at each developmental stage, from the design and fabrication of devices to performance evaluation and data analysis. Specifically, this review discusses the multistep fabrication of FETs, choice of bioreceptors for relevant biomarkers, operational conditions, measurement configuration, and outlines strategies to improve the sensing performance and reach the level required for clinical applications. Finally, this review outlines the expected progress to the future generation of FET‐based diagnostic devices and discusses their potential for detection of cancer biomarkers as well as biomarkers of other noncommunicable and communicable diseases. Abstract : This review highlights the multistep fabrication and application towards early‐stage cancer detection using field effect transistors. To make a highly advanced and continuous monitoring diagnostic device for future generations, various important parameters to improve the sensing performances were spotlighted towards the end product commercialization.